2010
DOI: 10.1243/09576509jpe852
|View full text |Cite
|
Sign up to set email alerts
|

Performance deterioration of the governing stage nozzle caused by solid particle erosion in the steam turbine

Abstract: In the steam turbine, solid particle erosion on a nozzle cascade is known to damage the profile and surface smoothness of the cascade, which increases the flow loss of steam. The present study aims to make clear the relations between nozzle loss and surface degradation, aerodynamic parameters, as well as the shape, location, and size of the erosion notch. A series of numerical simulations were conducted to model the aerodynamic performance of various existing eroded nozzles. The results indicate that the nozzl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The result of the SST k –ω turbulence model is the closest to the experimental results. 21 The maximum deviation is less than 2%. Therefore, the SST k –ω model is adopted.…”
Section: Model and Methodsmentioning
confidence: 92%
“…The result of the SST k –ω turbulence model is the closest to the experimental results. 21 The maximum deviation is less than 2%. Therefore, the SST k –ω model is adopted.…”
Section: Model and Methodsmentioning
confidence: 92%
“…Islam [4] observed that for a blade with a scalloped TE, the lack of TE material reduced the TE blockage, leading to a decrease in mixed-out boundary layer losses. For similar TE damage, Wang et al [3] found a com parable trend. Islam [4] hypothesized that this increased the base pressure, reducing the base pressure's contribution to loss, as indi cated by Denton [5], Sjolander et al [6] performed an extended study on two scalloped trailing edge blades.…”
Section: Introductionmentioning
confidence: 87%
“…overturning towards the PS b. undertuming towards the SS Studies by Wang et al [3], Islam [4], DeCecco [11], and Sjolander et al [6] conducted research concerning the aerody namic impact of material removal from the trailing edge of a tur bine vane or blade. The general consensus of these studies showed that scalloped trailing edges or trailing edges with significant cracking will cause a pitchwise shift in the total pressure deficit towards the suction surface.…”
Section: Loss Correlations To Ngv Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Although these approaches make possible to understand influences of gas turbine deterioration on plant performance quantitatively, mechanisms of the performance degradation cannot be clarified. On the other hand, computational fluid dynamics (CFD) simulations were used to understand mechanisms of loss increase in deteriorated gas turbines (Bouchard, D. et al, 2014;Edwards, R. et al, 2012;Wang, S.-S. et al, 2009). The authors also carried out CFD simulations for deteriorated gas turbine and steam turbine using real blade geometries measured at a power plant during a maintenance work (Yonezawa, K., et al, 2016(Yonezawa, K., et al, , 2017(Yonezawa, K., et al, , 2018(Yonezawa, K., et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%